Iowa pharmacy, 1880-1905 : an experiment in professionalism - Anderson, Lee (University of Iowa Press, 1989)
Popular culture remembers the settling of the Midwest as a golden era of unbounded opportunity, a time when every farm was a family farm and every farmer glowed with health. Pioneers in nineteenth-century Iowa, however, had to battle a formidable host of diseases during this golden era & mdash;malaria was endemic, smallpox and dysentery occurred in widespread epidemics, and typhoid, cholera, scarlet fever, and diphtheria had their seasons. Physicians in the growing Hawkeye State had little of the status and skill they command today, and herbalists, hydropaths, eclectics, Thomsonians, and homeopa.